2007
DOI: 10.1007/s10038-007-0158-x
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation in the NPY gene in 14 Indian populations

Abstract: NPY is a 36-aminoacid peptide expressed in several areas of the nervous system. Neuropeptide Y (NPY) receptors represent a widely diffused system that is involved in the regulation of multiple biological functions. The human NPY gene is located in chromosome 7. The functional significance of coding Leu7Pro polymorphism in the signal peptide of preproNPY is known. Six hundred and fifty four individuals of 14 ethnic Indian populations were screened for three mutations in the NPY gene, including Leu7Pro. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
3
6
0
1
Order By: Relevance
“…Our previous study reports the presence of Pro7 across many Indian populations, with a wide variation of allele frequencies across ethnicities. 33 These results are consistent with physiological predictions, as the T1128C risk allele causes radical changes in the tertiary structure of the signal sequence of NPY 34 and exhibits higher synthesis, processing and release of the active peptide, 35 which has more vasoconstrictor property, 36 a leading disturbance in BP homeostasis. 37,38 Limitations of the current study include small sample size and also focus on one ethnic group may limit the generalizability of findings to other ethnic groups.…”
Section: Discussionsupporting
confidence: 87%
“…Our previous study reports the presence of Pro7 across many Indian populations, with a wide variation of allele frequencies across ethnicities. 33 These results are consistent with physiological predictions, as the T1128C risk allele causes radical changes in the tertiary structure of the signal sequence of NPY 34 and exhibits higher synthesis, processing and release of the active peptide, 35 which has more vasoconstrictor property, 36 a leading disturbance in BP homeostasis. 37,38 Limitations of the current study include small sample size and also focus on one ethnic group may limit the generalizability of findings to other ethnic groups.…”
Section: Discussionsupporting
confidence: 87%
“…Ding (2003) reported that the Pro7 allele might have originated in the north of Europe and then spread to the neighboring regions, and the frequency showed a decreasing north to south gradient and also stated that the highest allele frequencies were found in the Nordic countries. Our earlier study revealed in no significant LD between leu7pro and other polymorphic sites in the Indian populations with varying Pro7 allele (Bhaskar et al, 2007). In fact, Leu7Pro polymorphism results in an amino acid change in the signal peptide of NPY from leucine, which has a hydrophobic aliphatic side chain amino acid, to proline, which has a cyclic structure.…”
Section: Discussionmentioning
confidence: 80%
“…Analysis of 3 promoter polymorphisms along with T1128C in a German population could not detect significant associations with alcohol dependence in either single SNP or haplotype analysis [26]. Our earlier study reports the presence of the Pro7 allele in many Indian populations [38], with a strictly restricted distribution in the allele frequencies across ethnicities. The frequency of the Pro7 allele has been reported to be 0.08 in Finns, 0.03 in Dutchmen [8] and virtually absent in Japanese [39,40] and Koreans [41].…”
Section: Discussionmentioning
confidence: 99%
“…The present study supports the results of the Mediterranean population by showing a positive association between G1258A and alcohol dependence. Our previous study documented a wide ethnic variation in the allele frequencies of many Indian populations for 1258 A>G polymorphism [38]. …”
Section: Discussionmentioning
confidence: 99%